Interface Engineering in CuInSe2 Solar Cells Using Ammonium Sulfide Vapors. Issue 6 (22nd May 2017) - Buffière, Marie; Lepetit, Thomas; Khelifi, Samira; El Mel, Abdel‐Aziz
Abstract : We report on a novel approach to engineer the surface of Se‐based chalcogenide thin films at room temperature by direct exposure to ammonium sulfide (AS) vapors, serving as a sulfur source. When applied to CuInSe2 (CISe) absorbers, the exposure to AS vapors leads to the progressive de‐oxidation and sulfidization of the surface of CISe thin films. The modification of the surface chemical state results in i) an improved coverage of the absorber by the chemical bath deposited buffer layer; ii) a modification of the doping profile of the absorber; and iii) an increase in the open circuit voltage of CISe/CdS/ZnO solar cells. These results are explained according to a possible passivation of Se vacancies by sulfur atoms at the surface of the absorber, occurring as a consequence of its exposure to the AS vapors. Abstract : A surface sulfidization method based on the use of S(NH4 )2 vapors was developed for Se‐based chalcogenide thin films. When applied to CuInSe2 thin films, this treatment results in the incorporation of sulfur into the surface region of the material, which leads to the improvement in the open circuit voltage of the corresponding solar cells. This work sheds light on the role of the adsorption of sulfur at the surface of the absorber.